2003
DOI: 10.1177/152660280301000410
|View full text |Cite
|
Sign up to set email alerts
|

Open versus Endovascular Repair of Para-Anastomotic Aneurysms in Patients Who Were Morphological Candidates for Endovascular Treatment

Abstract: Patients with PAA who were endograft candidates but who were treated with open repair experienced more morbidity and had more complications than patients treated with stent-grafts. If long-term follow-up demonstrates durable results, stent-graft repair may become the therapy of choice in PAAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 37 publications
0
19
0
4
Order By: Relevance
“…13 Endovascular techniques carry a number of potential advantages, as they may avoid general anesthesia and aortic clamping, reduce operative blood loss and transfusion requirements, shorten hospital stay, finally limiting the overall physiological stress associated with conventional open surgery. Gawenda et al 2 showed that endovascular repair is safe and effective in this particular setting, reducing perioperative morbidity and complication rates, as stated in previous cases. 10,11 Nevertheless, the "endovascular solution" in these cases has not yet been well defined and should be decided case by case, including different strategies of aneurysm exclusion and presenting with several issues and technical challenges.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…13 Endovascular techniques carry a number of potential advantages, as they may avoid general anesthesia and aortic clamping, reduce operative blood loss and transfusion requirements, shorten hospital stay, finally limiting the overall physiological stress associated with conventional open surgery. Gawenda et al 2 showed that endovascular repair is safe and effective in this particular setting, reducing perioperative morbidity and complication rates, as stated in previous cases. 10,11 Nevertheless, the "endovascular solution" in these cases has not yet been well defined and should be decided case by case, including different strategies of aneurysm exclusion and presenting with several issues and technical challenges.…”
Section: Discussionmentioning
confidence: 59%
“…1 Usually asymptomatic, it may present clinically as a pulsatile mass or less commonly complicated with rupture. 2,3 Natural history includes frequently life-threatening complications, such as embolization, rupture, and erosion into adjacent organs. Conventional surgical treatment is associated with high mortality rates, ranging from 3 to 70%, 1,2,4-6 due to technical challenges related to dissection through previous scarred operative sites, poor quality of arterial wall and frequent comorbidities of these typically elderly patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower invasiveness, as compared to classical surgery, and high efficacy of the exclusion of the aneurysmal sac from circulation amounting to 97-98% is evidence that the endovascular method is a full alternative to open surgery (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Surgical reintervention is complicated and associated with a high perioperative risk. The mortality rate is 17% for patients undergoing elective surgery and ranges from 66% to 100% in urgent operations [2]. Promising results of endovascular primary abdominal aortic aneurysm treatment prompts one to consider applying the method in order to manage complications following the previous open procedures.…”
Section: Introductionmentioning
confidence: 99%